Real-time monitoring and evaluation of energy efficiency and thermal management of data centers. (October 2015) - Lajevardi, Babak; Haapala, Karl R.; Junker, Joseph F.
Abstract: The rapid growth of IT industry and the miniaturization of semiconductors have resulted in substantial increase in energy consumption, power density of IT equipment and, subsequently, heat dissipated from data center racks. Metrics have been proposed to overcome these energy efficiency and thermal management challenges. Measuring the performance of the data centers using a combination of wisely chosen metrics can increase the opportunity for considerable energy reduction. A variety of metrics developed and applied for such evaluation are reviewed herein. The energy and cooling efficiency of a small data center is then evaluated by applying several metrics. To perform the analysis, real-time monitoring of 25 parameters over a period of six weeks was performed through design and implementation of a wireless monitoring network. The results are analyzed and current energy efficiency and thermal management issues are discussed with respect to the relative effectiveness of the various metrics.